Street lighting: sex‐independent impacts on moth movement. (13th June 2016) - Degen, Tobias; Mitesser, Oliver; Perkin, Elizabeth K.; Weiß, Nina‐Sophie; Oehlert, Martin; Mattig, Emily; Hölker, Franz
Summary: Artificial lights have become an integral and welcome part of our urban and peri‐urban environments. However, recent research has highlighted the potentially negative ecological consequences of ubiquitous artificial light. In particular, insects, especially moths, are expected to be negatively impacted by the presence of artificial lights. Previous research with light traps has shown a male‐biased attraction to light in moths. In this study, we sought to determine whether street lights could limit moth dispersal and whether there was any sex bias in attraction to light. More specifically, we aimed to determine sex‐specific attraction radii for moths to street lights. We tested these hypotheses by collecting moths for 2 years at an experimental set‐up. To estimate the attraction radii, we developed a Markov model and related it to the acquired data. Utilizing multinomial statistics, we found that attraction rates to lights in the middle of the matrix were substantially lower than predicted by the null hypothesis of equal attraction level (0·44 times). With the Markov model, we estimated that a corner light was 2·77 times more attractive than a wing light with an equivalentre attraction radius of c . 23 m around each light. We found neither sexual differences in the attraction rate nor in the attraction radius of males and females. Since we captured three times more males than females, we conclude that sex ratios are representative of operational sex ratios or of different flight activities. These results provide evidence for street lights to limit moth dispersal, and that they seem to act equally on male and female moths. Consequently, public lighting might divide a suitable landscape into many small habitats. Therefore, it is reasonable to assume (i) that public lighting near hedges and bushes or field margins reduces the quality of these important habitat structures and (ii) that public lighting may affect moth movement between patches. Abstract : The authors results provide evidence that street lights have a sex‐independent impact on moth movement. Thus, public lighting is likely to divide suitable landscapes into many small habitats. Inevitably attracted insects are eliminated directly or temporarily from the mating pool possibly followed by a substantial impact on population dynamics.